Oxidative stress and antioxidant biomarker responses after a moderate-intensity soccer training session - Mello, R.; Mello, R.; Gomes, D.; Andrade Paz, G.; Nasser, I.; Miranda, H.; Salerno, V. P. (Research in Sports Medicine, 2017)
The present study investigated the effects of a moderate-intensity soccer training session on the production of reactive oxygen species (ROS) and the antioxidant capacity in athletes along with the biomarkers creatine kinase and transaminases for lesions in muscle and liver cells. Twenty-two male soccer players participated in this study. Blood samples were collected 5 min before and after a moderate-intensity game simulation. The results showed a decrease in the concentration of reduced glutathione (GSH) from an elevation in the production of ROS that maintained the redox homeostasis. Although the session promoted an elevated energy demand, observed by an increase in lactate and glucose levels, damage to muscle and/or liver cells was only suggested by a significant elevation in the levels of alanine transaminase (ALT). Of the two biomarkers analysed, the results suggest that measurements of the ALT levels could be adopted as a method to monitor recovery in athletes.